The Association Between Sand Body Distribution and Fault of Zhuhai Formation on the North Slope of Baiyun Sag, Pearl River Mouth Basin, China - Geer Zhao; Rui Zhu; Zhenyu Si; Mengmeng Liu (Applied Sciences)
This paper is predominantly intended to explore the distribution rule of the sand body of the Zhuhai Formation on the north slope of the Baiyun Sag. The Zhuhai Formation was deposited during a rifting phase. Influenced by tectonic movements, the investigated area developed a set of contemporaneous normal faults extending in the near W-E direction. The formation of faults alters the palaeomorphology, exerting a certain influence on the distribution of sedimentary sand deposits. To clarify the correlation between faults and sand bodies will be advantageous for an even distribution of sand bodies in the Zhuhai Formation. This paper systematically integrates the results of previous research findings, drillcore logging and analysis, and 3D seismic data. The seismic sedimentology method is adopted to identify three types of fracture systems and four types of associations between the sand body distribution and faults in the investigated area. In line with the difference of the fault inclination and spatial relationship, faults can be divided into three types, namely, the graben-type, transition zone, and syntropy-type. Graben-type fault combinations exhibit the opposite dip. Syntropy-type fault combinations display the same dip. Transition zone faults intersect at a tiny angle. It is noteworthy that the existence of a fault will exert a certain influence on the sediment transport direction and distribution pattern. On the basis of the fault group classification, four associations between the sand body distribution and graben-type, transport-type, syntropy-ladder-type, and syntropy-lifting-type faults are identified by considering taking into account these base shape factors. The syntropy-ladder type is conducive to the extension of the sediment along the source direction. Both graben-type and syntropy-lifting-type faults can accumulate sediments. The transport type changes the direction of the sediment supply.